Analisis Pengaruh Penambahan Fly Ash Bottom Ash (FABA) terhadap Kuat Geser Tanah Disposal Aktual di Area TAL MTB PT Bukit Asam untuk Konstruksi Timbunan Jalan - Astrid Fadhilah; Bochori; Rendi Gilang Pratama (Mataram University, 2026)
Road embankment construction on soft soil frequently encounters technical challenges in the form of low bearing capacity and high deformation potential, which can adversely affect road stability and service life. This study aims to analyze the effect of Fly Ash Bottom Ash (FABA), a by-product of coal combustion, on improving the shear strength of actual soft soil obtained from the TAL MTB disposal area of PT Bukit Asam. The FABA contents applied were 15% and 25% by dry weight of soil. Laboratory testing was conducted using direct shear tests on both untreated soil and soil mixed with FABA. The test results indicate that the addition of FABA significantly enhances the soil shear strength parameters, particularly cohesion (c) and internal friction angle (ϕ). The highest improvement was observed in the soil mixture containing 25% FABA, demonstrating that FABA is effective in improving the mechanical properties of soft soil. Therefore, the utilization of FABA as a soil stabilization material not only provides an efficient technical solution for road embankment construction but also contributes to sustainable and environmentally friendly industrial waste management.